PERLINDUNGAN HAK KEKAYAAN INTELEKTUAL (HKI) DALAM MENGHADAPI PELANGGARAN: ANALISIS KASUS GAJAH DUDUK PALSU - Venia Utami Keliat; Naomi Clara Tamba (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The protection of Intellectual Property Rights (IPR), particularly trademark rights, plays a crucial role in ensuring legal certainty and safeguarding business actors from unfair competition practices. This study aims to analyze the forms of legal protection granted to PT Gajah Duduk as the registered trademark holder and the legal consequences imposed on PT Pisma Abadi Jaya for trademark infringement of the “Gajah Duduk” brand. This research employs a normative juridical method using statutory and case approaches, analyzed qualitatively based on primary, secondary, and tertiary legal materials. The results indicate that legal protection for PT Gajah Duduk is provided through the first to file system as regulated under Law on Marks and Geographical Indications Number 20 of 2016, Such protection is preventive and repressive. In this case, PT Pisma Abadi Jaya was legally and convincingly proven guilty of trademark infringement based on a final and binding court decision up to the cassation level at Supreme Court of the Republic of Indonesia. The legal consequences include imprisonment, fines, and potential civil compensation claims. This study concludes that Indonesia’s trademark protection system has provided legal certainty for registered trademark holders.